Salary Distribution of Civil Servants After Divorce: Comparative Study of Islamic Law and National Law - Khomala, Ratu; Syarif, Muh. Rasywan (Mazahibuna: Jurnal Perbandingan Mazhab, 2022)
This article reviews Islamic and National Laws on the distribution of salaries of Civil Servants after divorce. Field research was conducted using a sociological approach at the Belopa Religious Court, South Sulawesi. The results found that judges at the Belopa Religious Court, deciding divorce cases for civil servants in terms of salary distribution, did not apply Government Regulation Number 10 of 1983 to Number 45 of 1990 as a rule. Under the Compilation of Islamic Law, the judge only decides where the defendant is charged with iddah, mut’ah, house, and hadhanah. Meanwhile, law enforcement and justice should socialize related to legal problems where ordinary people can understand the legal consequences in society. The public should be able to understand the legal consequences of their divorce, especially civil servants.